The economics of health - Culyer, A. J (Elgar, 1991)
Health economics has, in recent years, become a major area of research in economics. This important collection presents a careful selection of the best articles and is classified according to eight fields within health economics. It thus provides a comprehensive cross section of the large and disparate literature on the subject. It forms, in a real sense, a mini-library which may be useful to teachers and researchers who wish to have these frequently cited articles easily to hand. It shouls also prove useful to the many economists who will have difficulty in gaining access to the very diverse sources from which the material has been drawn.
International library of critical writings in economics ; 12
Keywords: poskytování zdravotní péče; Delivery of Health Care; Models, Econometric; ekonomika lékařská; zdravotnické služby; ekonomie, ekonomika, ekonomika zdravotnictví; ekonometrické modely; Health Services; Economics, Medical